Identifikasi Proses Bisnis Penerimaan Santri Baru di Pesantren Mahasiswa Miftahul Khoirot melalui Implementasi Business Process Reengineering - Hidayat, Dwi Wahyu; Indriastiningsih, Erna; Nugrahadi, Bekti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to propose identification to the business process of admitting new students at Miftahul Khoirot Student Boarding School by adopting the concept of Business Process Reengineering (BPR). The admission of new students is a critical stage in maintaining the quality of education in pesantren, and BPR can help in identifying, redesigning, and optimizing this process to achieve efficiency, productivity, and better service. The BPR method is used to analyze, redesign, and implement the process with a more effective and innovative approach. The results of this proposal include simplification of intake steps, use of information technology, reduction of bureaucracy, and improved coordination between departments. It is expected that the implementation of this proposal will result in significant improvements in the admission process, reduce the time required, and increase the satisfaction of prospective students and related parties. This proposal provides a foundation for Miftahul Khoirot Student Boarding School to become more responsive and competitive in accepting new students